2008
DOI: 10.4161/psb.3.9.5965
|View full text |Cite
|
Sign up to set email alerts
|

The electrical response ofPhaseolus vulgarisroots to abrupt exposure to hydroquinone

Abstract: Previous reports have suggested the primary mode of action of the allelochemical hydroquinone involves disruption of root cell membrane transport. Here we report the effects of hydroquinone on common bean (Phaseolus vulgaris) plants. Growth of leaves, roots and stems were all inhibited by 14 day exposure to 0.01 mM or 0.25 mM hydroquinone. Chlorophyll fluorescence (Fv/Fm) was inhibited by 0.25 mM hydroquinone. The membrane potential of P. vulgaris root cortex cells briefly hyperpolarized and subsequently slowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
(49 reference statements)
1
6
0
1
Order By: Relevance
“…In relation to the present study, Li et al ( 2009 ) identified hydroquinone from Podophyllum hexandrum , which was found to enhance wheat seedling growth (Li et al, 2009 ). A similar pattern of effect was also observed for P. vulgaris , when 0.25 mM of hydroquinone inhibited the chlorophyll fluorescence and membrane potential (Keller et al, 2008 ). The literature revealed that hydroquinone is suppressive to plants but at the same time, it ameliorates growth and germination of seeds.…”
Section: Discussionsupporting
confidence: 72%
“…In relation to the present study, Li et al ( 2009 ) identified hydroquinone from Podophyllum hexandrum , which was found to enhance wheat seedling growth (Li et al, 2009 ). A similar pattern of effect was also observed for P. vulgaris , when 0.25 mM of hydroquinone inhibited the chlorophyll fluorescence and membrane potential (Keller et al, 2008 ). The literature revealed that hydroquinone is suppressive to plants but at the same time, it ameliorates growth and germination of seeds.…”
Section: Discussionsupporting
confidence: 72%
“…Many natural compounds derived from plant secondary metabolism are highly phytotoxic. It has been demonstrated that some natural products with high phytotoxic activity can induce severe alteration in plant growth due to induction of programmed cell death (PCD) (Ding et al 2007 ; Keller et al 2008 ) and restriction in cell division (Kuraś et al 2006 ; Soltys et al 2011 ; Teerarak et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…2007), naphthoquinones (Babula et al . 2009), hydroquinone (Keller et al . 2008) and olive oil mill wastewaters, which are rich in polyphenols and catechol (Ciniglia et al .…”
Section: Introductionmentioning
confidence: 99%